Role of L-Arginine in Pre-Eclampsia - Amin, Yasmeen; Javed, Naureen; Akram, Sidrah; Ashraf, Bushra; Batool, Shazia (Indus Journal of Bioscience Research, 2025)
Introduction: Although the precise mechanism is yet unknown, L-arginine has been shown to be useful against preeclampsia by reducing systemic symptoms. L-arginine remodeling activities are thought to improve the uterine spiral arteries, which are thought to be compromised during preeclampsia. Such research was not before carried out within our general community. Therefore, we wish to investigate the outcomes of the L-arginine group of pregnant patients who are at high risk. My research will be useful in treating preeclampsia in high-risk pregnancies by employing L-arginine. Materials & Methods: The current study conducted at Department of Obstetrics and Gynaecology, Unit 3 DHQ/ Allied Hospital 2 Faisalabad from 7 Sep 2023 to 07 March 2023. There were 100 high-risk pregnancies with ages ranging from 20 to 35 years old (50 in each group). Patients having a history of H/O renal illness and diabetes were not included. Patients receiving a placebo were placed in Group B, while those receiving L-arginine were placed in Group A. Women in group A received 300 grams of L-arginine (Amino Whey Sachet) once daily until delivery, while women in group B received a homologous placebo (starch) once daily until delivery. Data from both groups were recorded. Results: The study’s age range was 20 to 35 years old, with a mean age of 27.17 ± 4.18 years. The average age of the women in groups A and B was 27.18 ± 4.17 and 27.16 ± 4.17 years, respectively. 173 patients, or 74.57% of the total, were in the 20–30 age range. 44 (88.0%) of the patients in group A (L-arginine) and 33 (66.0%) of the patients in group B (placebo) in my study showed efficacy, with a p-value of 0.009, which is statistically significant. Conclusion: This study concluded that L-Arginine is very effective in the prevention of preeclampsia in high-risk Pregnancies.